The employability of Bachelor of Administrative Science Graduates from UiTM Sarawak / Shanty Jata Andrew Uni and Suryati Sahari - Andrew Uni, Shanty Jata; Sahari, Suryati (2010)
The main focus of this study are to find out the employability and relevant of these programmed offer to the students. The most important criteria in hiring fresh university graduates are their own soft skills, such as their intra-personal and interpersonal skills. Malaysian employers also give greater emphasis on a graduate’s major than his or her cumulative grade point average (CGPA) or reputation of graduating university in making hiring decisions. Our research focuses more on the employer in which our fresh graduates from Bachelor in Administrative Science UiTM Sarawak are employed.